Genomic Characterization and Antibiotic Resistance Profiles of Acinetobacter baumannii Isolates From Intensive Care Units in Vietnam - Thanh Truc Tran; Phuc Hoang Bui (International Journal of Microbiology)
Acinetobacter baumannii, an opportunistic pathogen, is responsible for a wide range of healthcare-associated infections (HAIs), particularly in patients in intensive care units (ICUs). Carbapenem-resistant A. baumannii (CRAB) is of particular concern due to its extensive multidrug resistance (MDR) and limited treatment options. In Vietnam, CRAB has become increasingly prevalent, with resistant mechanisms primarily attributed to the presence of blaOXA-23 and blaNDM-1 genes. This study investigates the clinical characteristics and genomic epidemiology of three CRAB isolates (ICU773, ICU400, and ICU399) from a tertiary-care hospital in Ho Chi Minh City. The isolates exhibited high resistance to a wide range of antibiotics, including carbapenems, aminoglycosides, and fluoroquinolones, while maintaining susceptibility to colistin. Whole-genome sequencing was used to analyze the genomic profiles, resistance genes, and sequence types of the isolates. All three isolates possessed blaOXA-23 and additional resistance genes such as blaADC and aminoglycoside-modifying enzymes (AMEs). MLST analysis revealed distinct genetic lineages, with ICU773 and ICU400 belonging to Sequence Types 2/195 and 2/Novel and ICU399 to Sequence Types 571/804. In silico analysis further identified several efflux pump genes and other resistance mechanisms, including the presence of the adeABC, adeFGH, and AbaQ pumps. These findings highlight the complexity of CRAB’s genomic diversity and resistance mechanisms in the region, underscoring the urgent need for continuous surveillance and novel therapeutic strategies to combat this growing healthcare threat.